Pengembangan modul pembelajaran Peluruhan Radioaktif untuk mata kuliah Fisika Atom dan Inti pada Program Studi S-1 Pendidikan Fisika - Oktova, Raden; Azizah, Sofia Nur; Sukarelawan, Moh. Irma (Berkala Fisika Indonesia : Jurnal Ilmiah Fisika, Pembelajaran dan Aplikasinya, 2024)
The development of a Radioactive Decay learning module for the Atomic and Nuclear physics course at Undergraduate Physics Education Study Program. The Atomic and Nuclear Physics course is one of the important and interesting subjects to study in the Physics Education Bachelor's study program. Still, learning has not progressed as expected because students find it difficult to understand abstract material, including radioactive decay. Therefore, learning media is needed as a tool for independent learning, and one type of appropriate learning media is a module. Research has been carried out to develop a learning module on radioactive decay in Indonesian that is suitable for use to support independent learning and to determine the level of student user satisfaction with the module developed. This research used the ADDIE (Analysis, Design, Development, Implementation, and Evaluation) development model. Before being tested with users, the feasibility of the module was validated using a questionnaire instrument by two material expert lecturers. An average feasibility level of 84.2% was obtained, which is included in the very feasible category. In the trial, the learning module was distributed as a PDF file to 25 students as a sample of users, and a user satisfaction level of 86.0% was obtained, which is in the very satisfactory category. The research results show that the module developed is suitable for independent learning.